EFEKTIVITAS SOSIALISASI MODUL KESEHATAN PROGRAM FAMILY DEVELOPMENT SESSION DALAM MEMBENTUK SIKAP KELUARGA PENERIMA MANFAAT - Dwi Rini Sovia Firdaus; Roni Jayawinangun (Universitas Pakuan, 2019)
This study was originated from the high rate of poverty and malnutrition in the southern part of Bogor, especially at Cikaret district. This research was conducted in order to analyze the level of effectiveness of communication in the socialization of the health module Within the Family Development Session program (FDS program). This study also analyses how the attitude of family benefit recipients in Cikaret South Bogor and determine the influence of communication effectiveness In socializing the health module of the FDS program against the attitude of the family beneficiaries. This research uses one independent variable, namely the effectiveness of communication and one dependent variable namely the attitude. The indicators used to measure the variables of effective communication is credibility, message content, clarity of message, and channel. The indicators used to measure the attitude variable of the recipient family benefits, are willingness, identification, and internalization. This research was conducted at Cikaret district in October 2018 to March 2019. This study uses a random technique based on the area (Cluster Sampling), meaning that the sampling was done based on groups or specific areas with a total of 100 beneficiary families. Analytical tools used in this research is regression analysis. Questionnaire, interview, and observation were used as data collecting techniques. This research applies two data analysing techniques, the descriptive statistical analysis technique and the statistical analysis non-parametric technique. The results of this research show that there is a positive and significant influence between the effectiveness of communication in the socialization of the health module of the Family Development Session program against the attitude of the family beneficiaries reaching 65.8%, while the rest of 34.2% influenced by other factors not present in this study. Keywords : Effectiveness Of Communication, Socialization, Family Development Session, Attitude